Penerapan Budaya Kerja ASN BerAKHLAK di Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Palembang - Nabila Nabila; Irwan Septayuda (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the implementation of the State Civil Apparatus (ASN) BerAKHLAK work culture at the Office of Women's Empowerment and Child Protection (DPPPA) Palembang City. The research is motivated by the demands of bureaucratic reform that emphasize cultural change through strengthening organizational culture based on ASN Core Values. The research method uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data triangulation was used to test the validity of the information. The results showed that the implementation of the seven ASN BerAKHLAK Core Values (Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative) has generally been well implemented at DPPPA Palembang City. This is reflected in employees' commitment to providing excellent service, compliance with regulations, efforts to improve competence, the creation of harmonious working relationships, loyalty to the organization, adaptability to change, as well as effective coordination and collaboration. However, the study also identified several obstacles that are still faced, including the adaptation process to policy and technological changes that takes time, the need for continuous improvement of employee competence, and challenges in cross-sector coordination and collaboration. The implications of this study emphasize the need for continuous improvement and development efforts so that the implementation of the ASN BerAKHLAK work culture can run more optimally in supporting the improvement of public service quality.